Genome-based epidemiology and antimicrobial resistance determinants of Neisseria gonorrhoeae isolates with decreased susceptibility and resistance to extended-spectrum cephalosporins in Argentina in 2011–16. (28th February 2019) - Gianecini, Ricardo A; Golparian, Daniel; Zittermann, Sandra; Litvik, Ana; Gonzalez, Silvia; Oviedo, Claudia; Melano, Roberto G; Unemo, Magnus; Galarza, Patricia; ,
Abstract: Objectives: Our aim was to describe the molecular epidemiology and antimicrobial resistance determinants of isolates of Neisseria gonorrhoeae with decreased susceptibility and resistance to extended-spectrum cephalosporins (ESCs) in Argentina in 2011–16. Methods: Gonococcal isolates ( n= 158) with decreased susceptibility and resistance to ESCs collected in 2011–16 across Argentina were subjected to WGS and antimicrobial susceptibility testing for six antimicrobials. Results: In total, 50% of the isolates were resistant to cefixime, 1.9% were resistant to ceftriaxone, 37.3% were resistant to azithromycin and 63.9% of the isolates showed an MDR phenotype. Resistance and decreased susceptibility to ESCs was mainly associated with isolates possessing the mosaic penA -34.001, in combination with an mtrR promoter A deletion, and PorB1b amino acid substitutions G120K/A121N. Phylogenetic analysis revealed two main clades of circulating strains, which were associated with the N. gonorrhoeae multiantigen sequence typing (NG-MAST) ST1407 and closely related STs, and characterized by a high prevalence rate, wide geographical distribution and temporal persistence. Conclusions: N. gonorrhoeae isolates with decreased susceptibility and resistance to ESCs in Argentina have emerged and rapidly spread mainly due to two clonal expansions after importation of one or two strains, which are associated with the international MDR NG-MAST ST1407 clone. The identification of the geographical dissemination and characteristics of these predominant clones may help to focus action plans and public health policies to control the spread of ESC resistance in Argentina. Dual antimicrobial therapy (ceftriaxone plus azithromycin) for gonorrhoea needs to be considered in Argentina.